KAJIAN TINGKAT WALKABILITY BERDASARKAN PERSEPSI MASYARAKAT PADA TROTOAR JALAN GAJAHMADA, PONTIANAK - Elizabeth, Cintya; Andi, Uray Fery; Alhamdani, Muhammad Ridha (JMARS: Jurnal Mosaik Arsitektur, 2026)
Sidewalk is a place for pedestrian activities which is equipped with adequate facilities to provide comfort for pedestrians. Some major streets usually have sidewalks, one of which is on Jalan Gajahmada in Pontianak. Jalan Gajahmada is included in the trade and service area with activities related to the economy characterized by the presence of shops, hotels, banks, offices and coffee streets. Currently, the function of sidewalks is not maximized as it becomes a selling area and even a place for parking vehicles. Jalan Gajahmada in Pontianak is included in the priority plan for developing and improving service centers, one aspect of area development is sidewalks for pedestrian facilities. This research aims to determine the level of walkability of Jalan Gajahmada Pontianak sidewalks. Measuring the level of walkability uses the perception of the community as respondents by referring to 9 walkability parameters modified by the Asian Development Bank (ADB). Data collection was obtained from distributing questionnaires to 50 respondents who had been active on the sidewalks of Jalan Gajahmada, Pontianak. The data results were analyzed using a quantitative descriptive method with a data centering system using the mean score to obtain a walkability value. The values obtained are then grouped into 3 levels of walkability using Sturges' rules. The research results showed that there were 4 variables with good quality, 2 variables with medium quality, and 3 variables with poor quality. The 3 variables included in poor quality are the availability of crossing facilities, supporting facilities, and disability support infrastructure.